Peran Ekstrakurikuler Kepramukaan Dalam Meningkatkan Karakter Siswa Di SMP Attin Namosain Kupang - Lae, Milen Yolanda; Selly, Frans Kristian; Lima, Stofiani Susana (Universitas Nusa Cendana, 2025)
This research was conducted at Attin Namosain Junior High School in Kupang City. The primary focus of the study was the influence of extracurricular activities on improving student character, with the aim of explaining the contribution of scouting efforts in fostering student character development at Attin Namosain Junior High School in Kupang. This study employed a qualitative descriptive methodology, providing a comprehensive overview of the implications of scouting. According to Sugiyono (2019:9), qualitative research is characterized by the researcher serving as the primary instrument, with data analysis conducted through an inductive approach. To collect relevant data, the researchers used techniques such as observation, interviews, and document analysis. The findings of this investigation indicate that initiatives aimed at improving student character are being implemented effectively. The study concluded that scouting plays a significant role, as evidenced by the character values developed through scouting activities and the role of the instructors in carrying out their roles. The extracurricular function of scouting plays a very influential role in improving student character. Scouting efforts provide important character values, including discipline, responsibility, cooperation, leadership, and social awareness among its members. Through numerous activities, students not only develop practical competencies but also cultivate stronger character, which then influences their attitudes and behavior in daily life. With the advancement of character development, students are expected to develop into better individuals and make constructive contributions to society.